COVID‐19: A threat to educated Muslim women's negotiated identity in Pakistan. Issue 5 (8th May 2020) - Safdar, Muhammad; Yasmin, Musarat
Abstract : This study attempts to explore how the lockdown/containment measures taken by the government during the COVID‐19 pandemic have threatened educated Muslim women's negotiated identity regarding wifehood and motherhood in urban Pakistan and how they struggle to reposition to reconstruct it. Through semi‐structured interviews, making an in‐depth comparative study of three differently situated cases (Muslim women), this study argues that the abnormal situation that has ensued from the pandemic has reinforced the vulnerability of women's nascent negotiated identity by landing them in a space where they are supposed by the normative structures to step back to carrying out their traditional responsibilities as 'good' wife and mother during the crisis. It has found that the pandemic has similarity in its impacts for the women in their familial lives, despite their being variously situated and resistive, due to the general religio‐culturally defined patriarchal social behaviour of the place (Pakistan) toward women and lack of action on the part of the state for implementing its laws of women's empowerment.